Domestication of Red Seaweed (Gelidium latifolium) in Different Culture Media - Andri Wijayanto; Ita Widowati; Tjahjo Winanto (Marine Science Department Diponegoro University, 2020)
Gelidium latifolium is one of red seaweed types potentially can be developed as an industrial raw material. Since Gelidium is currently taken from ocean, the availability of seaweed from aquaculture is necessary to overcome the small number of its availability in nature. In Indonesia, G. latifolium cultivation has not been carried out so that domestication is required. The use of macro and micro nutrients in growth media is essentially needed for the domestication process. Domestication requires fast media and place for growth. The purpose of this study is to determine the growth of biomass and the survival of G. latifolium in different culture media. The study was conducted in a semi-outdoor research laboratory. The method used in this research is laboratory experimental method and Completely Randomized Design (CRD) with the treatment applied using 3 types of culture media (Urea: Za: TSP) by comparison (A) 100: 50: 50% (2 g.L-1), (B) 75: 75: 50% (2 g.L-1) and (C) 75: 50: 75% (2 g.L-1), with 3 replications. The seaweed was kept in 10 L of water in aeration equipped aquarium and filled with 10 g of G. latifolium on each treatment. The best growth rate of G. latifolium biomass is 5.67± 0.58 g and 100±0% are survived in C culture medium with a concentration of 75% Urea: 50% ZA: 75% TSP (2 g.L-1).